Analisis Penguasaan Konsep Siswa dalam Menyelesaikan Soal Miskonsepsi pada Mata Pelajaran Biologi - Hajiriah, Titi Laily; Harisanti, Baiq Muli (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to describe students' mastery of concepts in solving misconceptions in biology subjects. The sample used is grade 12 students majoring in scienceÂ  and using purposive sampling as a sampling technique. The instrument used is in the form of open test questions containing misconceptions that have been validated by 2 experts and are considered valid because they come from a collection of misconceptions with ISBNs. Data analysis used in this study is the CRI technique. The results of the analysis of the research data can be concluded that the level of understanding of students through their CRI analysis is at a level > 2.5 with the category of misconceptions. Based on the results of the study, it can be concluded that grade 12 science students have very low mastery of concepts that trigger misconceptions so that it is necessary to review certain concepts that have been studied.